2013
DOI: 10.1016/j.ijid.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough bacteremia due to Clostridium tertium in a patient with neutropenic fever, and identification by MALDI-TOF mass spectrometry

Abstract: Clostridium tertium is rare in a human clinical specimen and its pathogenicity is often uncertain. However, the organism has been increasingly recognized as a cause of bacteremia and other infections in immunocompromised patients, especially those with hematologic malignancies. The diagnosis and treatment of C. tertium are difficult due to its growth pattern, micromorphology, and antibiotic resistance. The organism can easily be misidentified as Gram-positive aerobic rods such as Bacillus species, usually cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…[6,10] However, fatal cases of C. tertium bacteremia have been reported [2,5,8] and we believe that treatment must be initiated upon the identification of the bacterium in blood cultures. To date, although most documented cases have involved neutropenic patients, [2,[5][6][7][9][10][11] cases involving non-neutropenic patients have also been described. [2,4,7,8] Salvador et al [11] reported that C. tertium could be rapidly identified using a novel mass spectrometry technology (matrix assisted laser desorption ionization timeof-flight).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,10] However, fatal cases of C. tertium bacteremia have been reported [2,5,8] and we believe that treatment must be initiated upon the identification of the bacterium in blood cultures. To date, although most documented cases have involved neutropenic patients, [2,[5][6][7][9][10][11] cases involving non-neutropenic patients have also been described. [2,4,7,8] Salvador et al [11] reported that C. tertium could be rapidly identified using a novel mass spectrometry technology (matrix assisted laser desorption ionization timeof-flight).…”
Section: Discussionmentioning
confidence: 99%
“…To date, although most documented cases have involved neutropenic patients, [2,[5][6][7][9][10][11] cases involving non-neutropenic patients have also been described. [2,4,7,8] Salvador et al [11] reported that C. tertium could be rapidly identified using a novel mass spectrometry technology (matrix assisted laser desorption ionization timeof-flight). In this case, we believe that C. tertium was the cause of septicemia because the organism was independently cultured and that the bacterium identified in the anal wound cultures was different.…”
Section: Discussionmentioning
confidence: 99%
“…For C. paraputrificum, the pathogenic effect on its hosts has been historically attributed to the action of chitinases [22], whereas for C. tertium, sialidase production is more important [20]. However, misidentification during routine microbiological testing means that the virulence factors from these species have not been studied exhaustively [23]. The draft genomes for C. tertium and C. paraputrificum were recently published [24,25], where exploratory phylogenetic analysis (to differentiate genomes from their closest relatives) and virulencerelated factors and antimicrobial resistance genes were predicted by in silico analysis exclusively.…”
Section: Introductionmentioning
confidence: 99%
“…Several available diagnostic tools such as the detection of serum biomarkers (e.g. procalcitonin (PCT), interleukin (IL)-6, and IL-8) [3][4][5], polymerase chain reaction (PCR) [6,7], or mass spectrometry [8,9] could improve the management of FN. Although PCR analysis and mass spectrometry have the advantage of obtaining direct evidence of bacteria, the former could be susceptible to contamination with bacterial DNA [10][11][12][13][14], whereas the latter demonstrates insufficient diagnostic accuracy.…”
mentioning
confidence: 99%
“…Although PCR analysis and mass spectrometry have the advantage of obtaining direct evidence of bacteria, the former could be susceptible to contamination with bacterial DNA [10][11][12][13][14], whereas the latter demonstrates insufficient diagnostic accuracy. However, both methods might be useful for identifying causal bacteria from positive blood culture samples [7][8][9]. However, a strategy based on these tools has not been standardized for the management of FN.…”
mentioning
confidence: 99%